Improving the Knowledge and Skills of Posyandu Mothers Through Nutraceutical Training for Stunting Prevention in Darsono Village - Dewi Rashati; Asa Falahi; Anies Rohman D; Lindawati Setyaningrum; Dyan Wigati (Yayasan Daarul Huda Kruengmane, 2026)
Stunting remains a major nutritional problem that requires community-based preventive strategies. This community service program aimed to improve the knowledge and practical skills of Posyandu mothers regarding stunting prevention through nutraceutical training in Darsono Village. The program involved 30 participants using a one-group pretest–posttest approach. Activities consisted of educational sessions on stunting, critical prevention periods, nutraceutical concepts, and the benefits of turmeric, followed by practical training in preparing turmeric pudding as a functional food product. Knowledge changes were assessed using pretest and posttest questionnaires. The results showed improved participant knowledge across all measured indicators after the intervention. The greatest improvement was found in understanding nutraceutical concepts (33.33%), followed by knowledge of nutraceutical dosage forms (26.66%) and the benefits of nutraceuticals (26.66%). The training also strengthened participants’ practical ability to utilize local food resources as an innovative nutritional intervention. These findings suggest that combining health education with hands-on practice is an effective strategy to strengthen community capacity in stunting prevention.